Cytogenetic characterization of Guaiacum officinale, chromosome number and conservation management - VACHIRAPORN PIKULTHONG; BAGHER JAVADI; SUTHIRA MANEECHAI; METHANEE HOMTHONG; PIYAWAN SARAKIT; CHANTANA THONGPRAPHA; PUANGPAKA UMPUNJUN; SUPAJIT SRAPHET; ALONGKLOD TANOMTONG (Society for Indonesian Biodiversity, 2025)
Abstract. Pikulthong V, Javadi B, Maneechai S, Homthong M, Sarakit P, Thongprapha C, Umpunjun P, Sraphet S, Tanomtong A. 2025. Cytogenetic characterization of Guaiacum officinale, chromosome number and conservation management. Biodiversitas 26: 5468-5475. Guaiacum officinale, commonly known as lignum vitae (Kaew Chao Chom), is a tree species in the Zygophyllaceae family valued for its ecological and economic importance but threatened by overexploitation. Cytological studies of this endangered species remain scarce. This study presents the first cytogenetic analysis of G. officinale, focusing on both mitotic and meiotic processes. Root tip samples were collected between 05:00 and 12:00 to examine mitosis, while young flower buds were collected between 06:00 and 13:00 to analyze meiosis. Peak mitotic activity occurred at 10:00, although the very small chromosome size and limited spreading during slide preparation posed challenges for accurate counting. In contrast, meiotic analysis at 08:00 provided clear evidence of 12 bivalents at metaphase I, establishing a diploid chromosome number of 2n = 2x = 24. Chromosome pairing was generally regular, with occasional anomalies observed, but overall meiotic stability indicated high fertility and strong reproductive potential. These findings clarify the chromosomal behavior of G. officinale and demonstrate its diploid, cytologically stable nature. The results provide a critical baseline for understanding taxonomy and evolutionary relationships within Zygophyllaceae and offer essential guidance for conservation and sustainable management of this endangered species. These findings represent the first cytogenetic report of G. officinale in Thailand and provide baseline data for future taxonomic, genetic, and conservation studies of this threatened species.